Mathematics Textbook of Grade 5 Based on Bell Criteria - Andira, Trini; Herman, Tatang (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
This study aims to determine the suitability of grade 5 mathematics textbooks that meet the criteria of material suitability, methods of delivering material, physical characteristics of books, and book instructions for teachers based on Bell's criteria. This study uses a descriptive qualitative approach. Data collection uses documentation techniques in the form of books and observation techniques in the form of questions based on Bell's criteria. Data retrieval is done directly where the researcher conducts face-to-face meeting with the teacher at school. The data source of this study was obtained from the grade 5 Mathematics Book published by ESPS Erlangga Curriculum 2013 Revised 2016 on the Fractions Chapter. The results obtained indicate that the suitability of the material against Bell's criteria for the Fraction Chapter is in the very good category. the suitability of the method of delivering material is in the very good category, the suitability of the physical character of the book is in the good category, and the manual for the teacher is very good.